Semi-synthesis of novel cardamonin analogues and identification of a highly active Cu(II)-cardamonin complex that inhibits migration and induces apoptosis via inhibition of mTOR expression - Bin Break, Mohammed Khaled Ali (2018)
Lung cancer is considered a major health concern and is responsible for most cancer-related deaths. Nasopharyngeal carcinoma (NPC) is another type of cancer that is predominantly in China and has a low survival rate, which makes it a serious health issue. There is currently no cure for lung cancer and NPC, so it was decided to investigate derivatives of the highly bioactive natural product, cardamonin, for a potential drug candidate. 19 analogues of cardamonin were synthesised and tested against A549 (lung) and HK1 (NPC) cell lines. The techniques employed in synthesising the analogues were one-step reactions which included alkylation, acylation, reduction, condensation, cyclisation and complexation reactions. The analogues were fully characterised. MTS assay showed that several derivatives, such as the allyl derivative of cardamonin (2) and cardamonin’s Cu (II) complex (19), had more potent cytotoxic activities than cardamonin. Furthermore, the active analogues have generally demonstrated lower toxicity towards normal MRC5 cells. Structure-activity relationship (SAR) analysis showed the importance of the ketone and alkene groups for bioactivity, while substituting cardamonin’s phenolic groups with more polar moieties resulted in activity enhancement. As part of the SAR study and further exploration of chemical space, the effect of metal coordination on cytotoxicity was also investigated, but it was only possible to successfully obtain the Cu (II) complex of cardamonin (19), and the metal ion enhanced bioactivity. 19 was the most potent analogue possessing IC50 values of 13.2 µM and 0.7 µM against A549 and HK1 cells, corresponding to a 5- and 32-fold increase in activity, respectively. It was also able to inhibit the migration of A549 and HK1 cells. Mode of action studies revealed that 19 induced DNA damage in both cell lines resulting in G2/M-phase arrest, which further led to apoptosis via the activation of caspase-9 and caspase-3/7. Moreover, qPCR analysis showed that 19 inhibited the expression of the mammalian target of rapamycin (mTOR) by >50% in A549 and HK1 cells which indicated that it exerted its anticancer activity, at least in part, via inhibition of the mTOR signalling pathway. So molecular docking of cardamonin and 19 to mTOR was performed and the study showed that the higher activity of 19 might be due to formation of further hydrogen bond interactions with the receptor resulting in a higher binding free energy of -9.8 kcal/mol. Therefore, all these assays have further proven the high bioactivity of 19. However, further in vivo and animal model studies would have to be conducted in order to confirm the potential of 19 as an anticancer agent.